The role of the social relief of distress (SRD) in reducing food insecurity: a budget analysis of the resource allocation and expenditure of SRD fund in Western Cape, South Africa - Maluleke, Mikateko (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScFoodSc)--Stellenbosch University, 2021.